Silica Gel Powder Catalyzed Intermolecular Wittig Reaction of Fluorine-containing Stabilized Phosphorus Ylides with Ninhydrin in Solvent-free Conditions - Ramazani, Ali; Reza Kazemizadeh, Ali; Ahmadi, Ebrahim; Rahnema, Massoumeh (Asian Journal of Chemistry, 2010)
Protonation of the highly reactive 1 : 1 intermediates, produced in the reaction between triphenylphosphine and dialkyl acetylenedicarboxylates, by 2,2,2-trifluoroethanol leads to vinyltriphenylphosphonium salts, which undergo Michael addition reaction with conjugate base to produce the corresponding fluorine-containing stabilized phosphorus ylides. Silica gel powder was found to catalyze intermolecular Wittig reaction of the fluorine-containing stabilized phosphorus ylides with ninhydrin in solvent-free conditions at 92ºC in 30 min in high conversions.